Phenomenology of Hope and Despair: A Qur’anic perspective - Osmani, Noor Mohammad (Inter-disciplinary Press, 2008)
Hope is an intrinsic value towards success, victory, enthusiasm, and a positive attitude in life. It is the main driving force that leads one to strive for excellence. Despair, on the other hand, turns off the rays of hope and optimism, and keeps one constantly lagging behind. It perishes the victims from the inner roots. Al-Qur’an, the Holy Book for all Muslims, sheds lights on the issue and urges one to be optimistic and hopeful. It warns of severe punishments for persistent criminals and sinners; while, on the other hand, sheds rays of hope for Divine mercy and forgiveness to the repentant. The Qur’an condemns the phenomenon of despair outright. It is only attributed to the deviant and non-believers. The Qur’an relates hope with belief in Allah and religion, and despair with disbelief and atheism. (Qur’an 12: 87, 15: 56) It is the non-believers alone that quickly turn to despair and hopelessness. He collapses during distresses and adversaries. It is the irony of humans that when affluent, turn out to be proud, and during adversaries get collapsed and loose all hopes, leading sometimes to suicide. (Qur’an 11: 9). The present research would therefore aim to provide a clear picture of hope and despair from Qur’anic perspective. How does the Qur’an instil hope in the minds of common people? What are the qualities of the people who are optimistic and have a positive attitude in life? What about those pessimistic and hopeless? The research focuses on the Qur’anic ayat as the primary reference, and also on the traditions of the Prophets as the secondary source. The research is expected to instil some rays of hope in the minds of readers, and through their implementation would help them turn out as optimistic and positive human being.